Can ordinary people seek environmental justice in Bangladesh? : Analyzing through the lens of legal, policy, and institutional framework (Bangladesh Journal of Public Administration, 2021)
The study's overarching objective was to identify the pitfalls and bottlenecks in ensuring environmental justice on an equal basis embedded in the existing legal, policy, and institutional framework. The environmental victims were examined, and the opinions of the line experts were garnered. The study revealed that ordinary people could not seek justice to the court directly for environmental damage due to bubbles in the legal and policy framework. The courts suffer from various challenges like fuzziness in the jurisdiction, lack of legal advisors, and workloads. On the other hand, the court has no power to take cognizance of an offense independently. The wealthy and influential polluters are reluctant to respect the law due to insufficient punishment prescribed by the statutes. The victims are rarely compensated, and there are a few options to resolve the dispute in alternative ways. The provision of legal aid for the poor and disadvantaged people is not much helpful. The public departments are stuck with a lack of logistics and human resources. The jurisdictional overlapping, underlapping, and conflict of interest among the departments worsen monitoring, control, surveillance (MCS), and effective coordination. The regulatory framework does not welcome the community in decision-making and natural resource management. Hence, the study recommends legal and institutional reform. Policy initiatives are warranted for effective environmental governance, green growth, campaign, and volunteerism.